Chondroblastoma of the femoral head-surgical management, outcomes and clinical perspectives: a case report - Bhatti, Viveksheel; Mourougayan, Nithin Venkat; Harshvardhan, J. K. Giriraj (International Journal of Research in Orthopaedics, 2024)
Chondroblastoma is a rare benign tumor predominantly affecting the epiphyses of long bones, often presenting in the second decade of life. It is known for its potential to recur and cause joint complications despite its benign histology. This report details the case of a 12-year-old boy diagnosed with chondroblastoma of the femoral head, who underwent surgical treatment involving curettage and the use of synthetic hydroxyapatite (HA) bone substitutes. The patient presented with groin pain and limping, with imaging studies revealing an osteolytic lesion in the femoral head. A core needle biopsy confirmed the diagnosis. To manage the lesion, an anterolateral approach was used to perform extensive curettage, and the defect was filled with HA blocks. Postoperatively, the patient was managed with gradual weight-bearing and regular follow-ups. At five years, the patient exhibited normal hip function with no evidence of tumor recurrence, collapse of the femoral head, or osteoarthritis. This case demonstrates that the use of synthetic HA as a bone substitute in the treatment of chondroblastoma can effectively preserve joint integrity and function, providing a viable alternative to traditional grafting methods. The approach was successful in maintaining articular congruence and preventing complications, highlighting the potential benefits of synthetic materials in managing subchondral bone lesions.